Talent Management Phenomenon in Indonesia-Systematic Literature Review - Linawati, Diana; Aswad, Muhammad; Azis, Yudi (Jurnal Borneo Administrator, 2024)
Talent management has attracted substantial attention from industry and academia worldwide. In Indonesia, implementing talent management in the business sector has expanded with business and economic growth. Various organisations, both multinational companies and local companies, have adopted the concept of talent management as part of their human resources management strategy. However, despite this trend, many organisations in Indonesia have yet to embrace talent management fully. This article explores the phenomenon of talent management in Indonesia through a systematic literature review (SLR) approach. A total of 29 articles discussing talent management in Indonesia were examined. It is evident that while talent management is gaining traction in Indonesia, especially compared to neighbouring countries, significant gaps in the discourse surrounding this phenomenon exist in both the public and private sectors